Sewing hapiness : a year of simple projects for living well - Ishida, Sanae, author (Seattle, Washington : Sasquatch Books, 2016)
Twenty simple sewing projects are tied together with a thread of memoir that tells the story of how sewing brought Sanae Ishida profound happiness. Each seasonal project, specially designed to promote health, creativity, relationships and more, provides gentle inspiration to live your best life.
Includes bibliographical references and index.
In English text.
Keywords: Sewing; Dressmaking